The Role of the Principal as a Supervisor in Increasing the Effectiveness of Administrative Services at SMP Negeri 1 Bilah Hulu - Rohani, Siti; Junita, Junita; Anjar, Agus (Lembaga Riset Mutiara Akbar, 2024)
This research aims to examine the role of the principal as supervisor in strengthening the effectiveness of administrative services at SMP Negeri 1 Bilah Hulu. The focus of this research covers five main aspects: (1) the role of the principal in supervising school administration, (2) the influence of the principal's supervision on the effectiveness of school financial management, (3) the role of the principal in supervising facilities and infrastructure, (4) development of information systems to increase service effectiveness, as well as (5) challenges faced in implementing supervision of school principals. This research uses a qualitative method with a case study approach, where data is obtained through interviews, observation and documentation analysis. The research results show that school principals play a crucial role in improving administrative effectiveness through strict and consistent supervision. Principal supervision has been proven to be able to increase transparency in financial management, ensure maintenance of facilities and infrastructure, and support the development of a more effective school information system. However, the implementation of supervision still faces various challenges, such as limited resources and resistance from staff. The implications of this research emphasize that principals need to develop better adaptive strategies and supervisory skills to overcome these challenges. In this way, the role of the principal as supervisor can continue to be improved, so that the effectiveness of administrative services at SMP Negeri 1 Bilah Hulu becomes more optimal and supports the achievement of overall educational goals.